Maximal mouth opening in infants and toddlers with spinal muscular atrophy: a prospective controlled study - Jana Zang; Deike Weiss; Charlotte Dumitrascu; Julia Glinzer; Marie Wegner; Anna Strube; Jonas Denecke; Almut Niessen; Christina Pflug (Orphanet Journal of Rare Diseases)
Abstract Background Bulbar function is frequently impaired in patients with spinal muscular atrophy (SMA). Although extremely important for the patient’s quality of life, it is difficult to address therapeutically. Due to bulbar dysfunction, maximum mouth opening (MMO) is suspected to be reduced in children with SMA. However, no published MMO values exist for SMA children younger than 24 months. This study presents a novel approach to measuring MMO in infants and toddlers with SMA and compares it with healthy controls. Methods Children with SMA (0–24 months) who received disease-modifying therapy at a single neuropediatric center and similarly aged healthy children were prospectively recruited. MMO was measured using a cardboard scale and a custom-designed instrument. Results A total of 115 children were included (SMA = 24, healthy controls = 91). Inter-rater reliability between two examiners was excellent (ICC = 0.987, 95% CI 0.959 to 0.995), as was the reliability between the cardboard scale and the custom-designed instrument (ICC = 0.986, 95% CI 0.968 to 0.994). A mixed linear model showed a significant increase of MMO with age, and a significantly wider mouth opening in healthy controls (p < .001). Conclusion For future research, MMO can provide valuable information about the involvement of cranial nerves, particularly in the context of disease-modifying therapies, even at a very early age.